Arbuscular Mycorrhizal Symbiosis Triggers Major Changes in Primary Metabolism Together With Modification of Defense Responses and Signaling in Both Roots and Leaves of Vitis vinifera - Goddard, Mary-Lorène; Belval, Lorène; Martin, Isabelle R.; Roth, Lucie; Laloue, Hélène; Deglène-Benbrahim, Laurence; Valat, Laure; Bertsch, Christophe; Chong, Julie (Frontiers in Plant Science, 2021)
Grapevine (Vitis vinifera L.) is one of the most important crops worldwide, but is subjected to multiple biotic and abiotic stresses, especially related to climate change. In this context, grapevine culture could take advantage of symbiosis through association with arbuscular mycorrhizal fungi (AMF), which are able to establish symbiosis with most of terrestrial plants. Indeed, it is well established that mycorrhization improves grapevine nutrition and resistance to stresses, especially water stress as well as resistance to root pathogens. Thus, it appears essential to understand the effect of mycorrhization on grapevine metabolism and defense responses. In this study, we combined a non-targeted metabolomic approach and a targeted transcriptomic study to analyze changes induced in both roots and leaves of V. vinifera cv. Gewurztraminer by colonization with Rhizophagus irregularis (Ri). We show that colonization of grapevine with AMF triggers major reprogramming of primary metabolism in roots, especially sugar and fatty acid metabolism. Whereas mycorrhizal roots had decreased contents in most sugars and sugar acids, a significant increase in several fatty acids (C16:1, linoleic and linolenic acids and the C20 arachidonic and eicosapentaenoic acids) was measured; however, a downregulation of the JA biosynthesis pathway was evidenced. We also found strong induction of expression of PR proteins from the proteinase inhibitor (PR6) and subtilase (PR7) families in roots, suggesting that these proteins are involved in the mycorrhiza development, but could also confer a higher resistance to root pathogens. Metabolic changes induced by mycorrhization were less marked in leaves, but involved higher levels of linoleic and linolenic acids, as well as decreased sucrose, quinic and shikimic acid contents.In addition, Ri colonization resulted in enhanced JA and SA levels in leaves. Overall, this study provides a detailed picture of metabolic changes induced by AMF colonization in a woody economically-important species. In addition, stimulation of fatty acid biosynthesis and PR protein expression in roots as well as enhanced defense hormone contents in leaves establish first insight in favor of a better resistance of grapevine to various pathogens provided by AMF colonization.